Pengaruh Faktor Lokasi, Produk Dan Harga Terhadap Keputusan Pembelian Konsumen di CV. Creative Centre - Ricky; Johannes; Johnny Chandra (LPPM STIE EKA PRASETYA, 2021)
This study aims to determine the effect of Location, Products and Prices on Purchasing Decisions at the CV. Creative Centre. The population in this study are all consumers who have made purchases on the CV. Creative Centre for 2019. By using the Slovin formula with an error rate of 10%, a total sample of 93 respondents was obtained. The results of the research analysis show that Location, Product and Price partially have a positive and significant effect on Purchasing Decisions at CV. Creative Centre. The results showed that Location, Product and Price simultaneously have a positive and significant effect on Purchasing Decisions at CV. Creative Centre. The results of this study are supported by the value of R square (R2) which means that the Location, Product and Price have an effect on the Purchasing Decision at the CV. Creative Centre. While the remaining is effectd by other factors originating from outside the research model such as service, perception, image, distribution channels, communication, advertising and price discounts